Case report: Almonertinib in combination with bevacizumab for leptomeningeal metastases from epidermal growth factor receptor-mutation non-small cell lung cancer: Case series - Zhang, Yuhai; Zhang, Meilin; Cheng, Wanwan; Fang, Shencun (Frontiers in Oncology, 2022)
Leptomeningeal metastasis (LM) is a lethal complication of advanced non‐small cell lung cancer (NSCLC) with rapid deterioration and poor prognosis. It has no standard treatment for epidermal growth factor receptor mutation (EGFRm) NSCLC, and improving the clinical outcomes for patients with LM has become an urgent problem in clinical treatment. Both almonertinib and bevacizumab are capable of crossing the blood–brain barrier with comparable central nervous system effectiveness. To date, the almonertinib treatment in combination with bevacizumab in EGFRm NSCLC with LM has not been studied. We herein present five cases to further evaluate the effectiveness and tolerability of almonertinib in combination with bevacizumab for patients with EGFRm NSCLC and LM. For the first time, we report that almonertinib plus bevacizumab can not only effectively improve the neurological symptoms caused by LM but also prolong the survival time of patients with limited and controllable side effects, which provided a novel therapeutic approach for LM from EGFRm NSCLC.